(untitled) (Prilozi za orijentalnu filologiju, 2024)
German Saxon miners played an active role in the exploitation of the rich mineral deposits in Bosnia and Serbia throughout the Middle Ages and in the enrichment of the region. After the conquest of Istanbul, during the reign of Mehmed the Conqueror, these rich mineral deposits were gradually captured and incorporated into the Ottoman borders. As a matter of fact, the Ottoman bureaucracy made great efforts to ensure the continuous operation of these mining areas through the nazirs as well as the kâdi and the emin. Accordingly, the mines in what is today the majority of Macedonia, western Bulgaria, Ko- sovo and the southern parts of Serbia were transformed into a mukataa under the name of the Nezaret of Skopje to be administered from a single source. The silver and gold from these mines were converted into coins at the mints of Novo Brdo, Skopje and Kratovo, located close to the region. Although previous studies have provided information about the people involved in the exploitation of a mine, these are generally evaluated in the context of law codes. In particular, the information on katips is limited, and there is no de- tailed information on how many people served in a mine, what the process was for their appointment and dismissal, how much they were paid, whether there were wage differences between mines, and whether the wage balance varied from mine to mine. This study focuses on the work and remuneration of the scribes (maden, chashni, potok, tsarh, rosht, kalhane and sarraf), especially the kâdis who took part in the supervision phase of the mines and the scribes who recorded every stage of the mines, as well as the scribes who took office with the preference of the refugee and the salaries they received in return for their work. In addition, the nazirs, who assumed an important role in the control of the mukataas, and the military officers who assisted them in fulfilling this task were evaluated. In particular, the literature provides enlightening information about the katips who worked in the mining areas, the jobs they performed, the issues that were taken into consideration in their appointment and dismissal, and the salaries they received while performing these jobs.